2013
DOI: 10.1002/ange.201302740
|View full text |Cite
|
Sign up to set email alerts
|

Domino Synthesis of Fluorine‐Substituted Polycyclic Aromatic Hydrocarbons: 1,1‐Difluoroallenes as Synthetic Platforms

Abstract: Dominoeffekt: 1,1‐Difluorallene mit einem Aryl‐ und einem Cyclopentenring reagieren in Indium(III)‐katalysierten Friedel‐Crafts‐Cyclisierungen mit anschließender Ringerweiterung und Dehydrierung in hohen Ausbeuten zu fluorierten polycyclischen aromatischen Kohlenwasserstoffen. Die Einführung einer Ar‐Gruppe gelang durch In‐situ‐Halogenierung der intermediären Indiumspezies und anschließende Suzuki‐Miyaura‐Kupplung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…While using 1-(trifluoromethyl)alkenes (1, R = (hetero)aryl) such as 1w-1x as substrates, C-Cu bond formation may be electronically favored at the benzylic position stabilization by the (hetero)aryl group (C 0 ). [57][58][59][60][61][62] After further enantioselective formation of intermediate D, cis b-F elimination [33][34][35][36][37][38][39][40][45][46][47][48][49] delivers the final product 3 and a CuF-like species E, which can undergo anion exchange with NaO t Bu to regenerate the copper catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While using 1-(trifluoromethyl)alkenes (1, R = (hetero)aryl) such as 1w-1x as substrates, C-Cu bond formation may be electronically favored at the benzylic position stabilization by the (hetero)aryl group (C 0 ). [57][58][59][60][61][62] After further enantioselective formation of intermediate D, cis b-F elimination [33][34][35][36][37][38][39][40][45][46][47][48][49] delivers the final product 3 and a CuF-like species E, which can undergo anion exchange with NaO t Bu to regenerate the copper catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Defluorinative functionalization of fluorine-containing compounds has shown promise as it confers synthetic versatility to inert C-F bonds. [33][34][35][36][37][38][39][40] Defluoroborylations of…”
Section: Introductionmentioning
confidence: 99%
“…Electron-rich as well as electron-poor substrates underwent the transformation. The presence of halogen substituents [Cl (16, and 23), F (18, 19, 20, 22, and 25)], ethers [OCH 3 (15), SCH 3 (26)], amides [CONEt 2 (10)], and acids [COOH (24)] were tolerated. For the synthesis of 13, 14, and 15, a larger excess of base (conditions b) was required, whereas for the chlorinesubstituted product, 16, four equivalents (conditions c) were enough to observe full conversion.…”
Section: Resultsmentioning
confidence: 99%
“…However, allylic trifluoromethyl13 and difluoromethyl groups14 display a lower activation barrier and can undergo substitution with carbon and nitrogen nucleophiles through a S N 2′ mechanism. For instance, difluoroallenes15 and β,β‐difluorostyrenes16 were reported to be versatile substrates for the preparation of fluorine‐substituted PAHs and 3‐fluorinated isoquinolines.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of effective intramolecular aryl-aryl coupling via C-F bond activation under transition-metal free conditions might be a solution to this problem. Recently, Siegel et al [21], Ichikawa et al [22], and Amsharov et al [23,24] have demonstrated the efficiency of the C─F bond activation strategy for the synthesis of various bowl-shaped PAHs via formal HF elimination step (cyclodehydrofluorination). In the last case, the effective cyclization was achieved utilizing easily accessible aluminum oxide, which makes the approach highly attractive for preparative-scale synthesis.…”
Section: Wet-chemical Synthesismentioning
confidence: 99%